Perancangan Ulang Produk Pti 1 Menggunakan Metode Reverse Engineering (Studi Kasus Di Laboratorium Teknik Industri,Universitas Muhammadiyah Surakarta) - Wibowo, Ganang Fitrianto, Ratnanto Fitriadi, ST., MT (2016)
Referring to ABET and BKSTI, UMS has a purpose industrial engineering engineering education, by providing practical engineering experience. Laboratories is the answer, because the lab is the heart of engineering education program, UMS industrial engineering lab is divided into 3 basis unctions. Basic lab work is the introduction of pplications in industrial, lab support for analytical and statistical modeling in industrial engineering and industrial engineering design lab (PTI). PTI practicum is an integrated lab of the semester 3 to the 6th semester, divided into 4 main aspects of product design PTI 1, PTI 2 design of work stations, 3 suplly chain management PTI, PTI 4 facility layout design and creative industries. Practical PTI 1 product design is a lab that produces a line of toys are made from mahogany, the last period made products PTI 1 with the theme of sports cars, using controls with pedal (using an AC motor and control cables). The purpose of this study is to identify the implementation and evaluation of practicum PTI 1 by the practitioner and assistant, designing products Car PTI 1 creative and innovative use of Android-based propulsion systems using reverse engineering methods. According wibowo (2006) reverse engineering (RE) is an activity of analysis an existing product is used as a reference for designing a new product with the development of the components of a particular product. RE Activity 1. Activity 2. Assembly product disassembly of product 3. Benchmarking 4. Designing a new product 5. Preparation of the prototype. RE done on remote control products and products PTI 1 peiode last car. Identification and evaluation of practicum PTI 1 was conducted by distributing questionnaires to three forces are already implementing pratikum PTI 1 and also from Asisiten. For the development of products made with innovation in product materials, namely wood, concrete iron Eser, acrylic and aluminum for the chassis and body, engine (android based control system and DC motor drive systems). the components of the battery lippo 7.4 v, arduino uno, Bleutooth hc-05 and the relay 5v single chanel, R540 motors, belt and pulley.